PENUNTUN PRAKTIKUM BERBASIS GREEN CHEMISTRY PADA MATERI SEL VOLTA - Fitri, Amelia Ramadhani; Yusbarina, Yusbarina; Utami, Lisa; Octarya, Zona (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
Voltaic cell practical work using synthetic chemicals can produce waste that damages the environment, so environmentally friendly substitute materials are needed. Green Chemistry based practical work was not available yet at State Senior High School 1 Rambah, Rokan Hulu. This research aimed at knowing validity and practicality levels of Green Chemistry based practical work on Voltaic Cell topic designed. It was Research and Development with DDR model consisting of 3 steps–planning, designing and developing. This research was conducted to the twelfth-grade students of MIPA at State Senior High School 1 Rambah, Rokan Hulu. Based on research findings, Green Chemistry based practical work on Voltaic Cell topic designed showed that the validity percentages by material and media experts continuously were 96.66% and 94.12% with very appropriate criteria (valid). The practicality percentages of Chemistry subject teacher and student respond continuously were 88% and 92,9% with very practical criteria. Based on the data, it could be concluded that Green Chemistry based practical work designed was very appropriate and very practical to be used as a teaching material in supporting the implementation the practical work on Voltaic Cell topic.